(untitled) (Research, Society and Development, 2024)
Objective: To analyse scientific publications on the importance of fundamental nursing practices. Methods: A descriptive exploratory review with a qualitative approach was carried out using the following databases: Web of Science and Cochrane Library (SCOPUS), Brazilian Bibliography (BDENF), Online Medical Literature Search and Analysis System (MEDLINE/PUBMED) and Latin American and Caribbean Health Sciences Literature (LILACS). Using the descriptors with the aid of the Boolean operator "and". Results: According to the theoretical framework, fundamental practices influence the quality of care provided by nurses and undergraduate nursing students. It is also possible to verify that during their undergraduate studies, students who practice a wide variety of techniques under the direct supervision of their teacher show greater confidence in their work. Conclusion: Therefore, the dynamic between theoretical content and practice is essential for training nurses who are critical, reflective, humanized, competent and able to relate previous knowledge to their practice.